Endoscopic Tympanomastoid Surgery - Our Experience - Sukamal Das (Bengal Journal of Otolaryngology and Head Neck Surgery, 2014)
Introduction In last few decades medical science has seen resurgence of minimally invasive surgery by development of endoscopes with adequate illumination, magnification and image quality. Although operating microscope made a significant advance in ear surgery but it has a drawback of unobservable blind angles in cavities of middle ear.